Antimicrobial photodynamic therapy combined with periodontal treatment for metabolic control in patients with type 2 diabetes mellitus: study protocol for a randomized controlled trial - Evangelista, Erika Elisabeth (Trials, 2015)
BACKGROUND: The relationship between diabetes mellitus (DM) and periodontal disease is bidirectional. DM is a predisposing and modifying factor of periodontitis, which, in turn, worsens glycemic control and increases proteins found in the acute phase of inflammation, such as C-reactive protein. The gold standard for the treatment of periodontal disease is oral hygiene orientation, scaling and planing. Moreover, systemic antibiotic therapy may be employed in some cases. In an effort to minimize the prescription of antibiotics, photodynamic therapy (PDT) has been studied as an antimicrobial technique and has demonstrated promising results. The aim of the proposed study is to determine whether PDT as a complement to periodontal therapy (PT) is helpful in the metabolic control of individuals with type 2 diabetes and the reduction of acute-phase inflammatory markers. METHODS/DESIGN: The patients will be randomized using a proper software program into two groups: 1) PT + placebo PDT or 2) PT + active PDT. All patients will first be examined by a specialist, followed by PT performed by two other healthcare professionals. At the end of each session, PDT (active or placebo) will be administered by a fourth healthcare professional. The following will be the PDT parameters: diode laser (660 nm); power output = 110 mW; exposure time = 90 s per point (9 J/point); and energy density = 22 J/cm(2). The photosensitizer will be methylene blue (50 μg/mL). The patients will be re-evaluated 15, 30, 90 and 180 days after treatment. Serological examinations with complete blood count, fasting glucose, glycated hemoglobin and salivary examinations to screen for tumor necrosis factor alpha, interleukin 1, interleukin 6, ostelocalcin, and osteoprotegerin/RANKL will be performed at each evaluation. The data will be statistically evaluated using the most appropriate tests. DISCUSSION: The results of this study will determine the efficacy of photodynamic therapy as an adjuvant to periodontal treatment in diabetic patients. TRIAL REGISTRATION: The protocol for this trial was registered with Clinical Trials registration number NCT01964833 on 14 October 2013.